The influence of ultrasound on the reaction of immobilized enzymes - ROSENFELD, Eike; SCHMIDT, Peter (Archives of Acoustics, 2015)
The effect of ultrasonic waves in the MHz range on the activity of immobilized a-amylase and glucoamylase was investigated. Measurements of the catalytic efficiency were carried out in a flow cell, in dependence on the concenration, the flow rate, and the molecular weight of the substrate, as well as on the size of the carrier particles (porous polystyrene). The results show that the ultrasonic effect might be explained by the promotion of the diffusion processes predominately within the Nernst diffusion layer of the carrier beads.